New standard encyclopedia. Vol. ONe / Robert B. Downs - Downs, Robert B. (1971)
Some of the many subjects covered, agriculture, animals, anthropology, architecture, art, biography, business and economics, chemistry, communitacion, educacion, greology, government, history, hobbies and recreation, homemaking, industry, literature and language, mathematics, medicine and health, military and naval science, music and drama, physics, plants, religion, space, sports, transportacion.